Clinical and laboratory characteristics of hemophagocytic lymphohistiocytosis induced by Leishmania infantum infection - Qi Shi (Public Library of Science (PLoS), 2021)
Background Visceral leishmaniasis (VL) could progress to secondary hemophagocytic lymphohistiocytosis (HLH), which is a rare but life-threatening condition with poor prognosis. So far, the clinical and laboratory characteristics of VL associated HLH have not been well elucidated. Method and findings In this study, we retrospectively analyzed the clinical and laboratory profiles between 17 patients with VL associated HLH and 27 patients with VL alone admitted at the Beijing Friendship Hospital, Capital Medical University from May 2016 to March 2021. In addition to the identification of Leishmania infection, hemophagocytosis was identified in bone marrow in the most cases of VL associated HLH (15/17). The patients with VL associated HLH had higher chances of bleeding, hepatomegaly, thrombocytopenia, hypertriglyceridemia, hyperferritinemia, hypofibrinogenemia, elevated secretion of soluble IL-2 receptor or lower NK cell activity compared to patients with VL only. Furthermore, patients with VL associated HLH had higher inflammation status associated with higher levels of Th1 (TNF-α, IFN-γ, IL-1beta, IL-6, IL-8, IL-12p70), Th2 (IL-4) and Th17 cytokines (IL-17, IL-23) in the peripheral blood, and higher parasite load (qPCR and parasite culture). All 27 VL cases were totally recovered after being treated with Sodium Stibogluconate, five of the 17 patients with VL associated HLH died even after timely treatment with anti-parasite and immunosuppressive chemotherapy. Conclusion Without appropriate treatment, visceral leishmaniosis could develop to secondary HLH. The parasite culturing and qPCR detection of bone marrow samples facilitates the diagnosis of VL associated HLH in addition to other findings of HLH. Prompt treatment with anti-Leishmania and immunosuppressive chemotherapy is critical to reduce the mortality of VL associated HLH. Author summary Hemophagocytic lymphohistiocytosis (HLH) is a rare but life-threatening syndrome characterized by pro-inflammatory cytokine secretion, hyperinflammatory and multiple organ damages. Visceral leishmaniasis (VL) is a well-known cause of infection associated HLH and result in fatal consequence. However, it is not well characterized for the clinical and laboratory features of the visceral leishmaniasis associated HLH. In this study, we presented that, compared to the VL alone, patients with VL associated HLH had higher chances of bleeding, hepatomegaly, thrombocytopenia, hypertriglyceridemia, hyperferritinemia, hypofibrinogenemia, elevated secretion of soluble IL-2 receptor or lower NK cell activity. Moreover, patients with VL associated HLH also had higher levels of Th1, Th2 and Th17 cytokines in the sera and had higher parasite load in the bone marrow specimen. More cases with VL associated HLH had hepatosplenomegaly with iron overload in the magnetic resonance imaging. In the therapeutic strategy, besides the anti-Leishmania treatment, anti-inflammatory therapy to reduce cytokine storm and excessive immune responses facilitated the remission in the VL associated HLH cases.